Beasts in the Garden: Human-Wildlife Coexistence in India's Past and Present - Oommen, Meera Anna (Frontiers in Conservation Science, 2021)
Human-wildlife encounters are characterised by a diverse array of engagements located on the continuum between the negative and the positive. In India, protracted conflict with wildlife is reflected in violence across a range of rural and urban ecologies, but is only one aspect of the multiple facets of ongoing human-non-human encounter. Within these shared spaces, there are often equally significant elements of acceptance, tolerance and reverence. Together, these are dependent on context, and can be explored via lived experiences and worldviews, and a moral economy of human-wildlife and human-human relationships. Historically, though hardly static, such relationships have been mediated by the ontological positioning of traditional societies and their embedded rules and practices. In recent years, these tenuous equilibria have been disrupted by top-down catalysts, including universalist conservation agendas percolating from the state and the global arena. This study aims to explore the changing nature of coexistence by using several historical and contemporary vignettes in relation to key species that routinely ‘transgress’ from their primary natural habitats into the ‘garden’ spaces of human cultivation and habitation. The study will argue that a deeper engagement with insights at the intersection of environmental history, political ecology and anthropology can improve our understanding of human-wildlife coexistence in India as well as across the world.